2008
DOI: 10.1001/archotol.134.12.1305
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor A and Proliferation Marker in Prediction of Lymph Node Metastasis in Oral and Pharyngeal Squamous Cell Carcinoma

Abstract: To explore the effect of Ki-67 and vascular endothelial growth factor A (VEGF-A) expression on the risks of advanced T category (T3,4) and positive lymph node involvement (Nϩ) in oral and pharyngeal squamous cell carcinoma (SCC) compared with laryngeal SCC. Design: Immunohistochemical analysis of prospectively recruited patients. Setting: University-affiliated hospital. Patients: A total of 147 previously untreated patients with different stages of SCC in the oral cavity, pharynx, and larynx. Main Outcome Meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 33 publications
(72 reference statements)
1
36
0
2
Order By: Relevance
“…Moreover, VEGF-A expression in another study was reported to be associated with advanced T stage for oral, pharyngeal, and laryngeal squamous cell carcinoma. However, the association with nodal status was significant only for oral and pharyngeal carcinoma (Table 1) [50]. In the same study, the combined overexpression of VEGF-A and the proliferation marker Ki-67 in oral and oropharyngeal squamous cell carcinoma was documented to demonstrate a significantly higher likelihood ratio for positive lymph nodes.…”
Section: Vegf and Lymph Node Metastasismentioning
confidence: 74%
See 1 more Smart Citation
“…Moreover, VEGF-A expression in another study was reported to be associated with advanced T stage for oral, pharyngeal, and laryngeal squamous cell carcinoma. However, the association with nodal status was significant only for oral and pharyngeal carcinoma (Table 1) [50]. In the same study, the combined overexpression of VEGF-A and the proliferation marker Ki-67 in oral and oropharyngeal squamous cell carcinoma was documented to demonstrate a significantly higher likelihood ratio for positive lymph nodes.…”
Section: Vegf and Lymph Node Metastasismentioning
confidence: 74%
“…Again in this study it was suggested that the combined expression of VEGF-A and Ki-67 was more effective in predicting positive nodal status in early local tumors compared to more advanced disease. In addition, patients with early oral and oropharyngeal carcinoma could be divided into high or low risk groups for occult metastasis on the basis of biological expression of these markers [50]. So far, it remains uncertain whether VEGF-A acts directly as a lymphangiogenic factor or via the induction of other associated molecules.…”
Section: Vegf and Lymph Node Metastasismentioning
confidence: 99%
“…12 Boonkitticharoen also found no correlation between this marker and metastases. 13 A recent Asian study reported a close association between VEGF-C/VEGFR-3 expression and lymph node metastases in squamous cell carcinomas of the larynx. The expression of these markers was positive only in the analysis of cervical metastases, and did not correlate with age, gender, T stage, or primary location of the laryngeal lesion.…”
Section: Discussionmentioning
confidence: 99%
“…26 A positive correlation between overexpression of VEGF protein or mRNA in cancer tissues and lymph node metastasis has also been reported in head and neck SCCs 23,29 as well as oral and pharyngeal SCCs. 28 VEGF can promote tumor growth because it can increase neovascularization. We further explained why VEGF can augment lymph node metastasis as follows.…”
Section: Discussionmentioning
confidence: 99%
“…21 VEGF is also found to be an important angiogenic cytokine for neovascularization in head and neck cancers. 22e29 Overexpression of VEGF mRNA or protein has been reported to be significantly related to poor prognosis and shorter survival 22e27 as well as positive lymph node metastasis 23,28,29 in head and neck cancer patients. In this study, we evaluated whether the VEGF mRNA level of OSCC surgical specimens could be a crucial biomarker to predict the progression, recurrence, and prognosis of OSCCs.…”
Section: Introductionmentioning
confidence: 99%